Judicial Characteristics and Judicial Decision-Making Study, 1955 - Nagel, Stuart S. ([Verlag nicht ermittelbar], 1984)
This study collected information on the judges serving on American state supreme courts and the United States Supreme Court in 1955. Background data were obtained from standard biographical sources, and judicial decision measures were derived from court records. The variables assessed party identification, organizational affiliations, judicial decision scores in over a dozen separate areas, and the career history of judges.